Effect of Karun River on the salinity status in the Shatt Al-Arab River, Basrah - Iraq - Al-Mahmood, Hassan K.; Mahmood, Ali B. (Mesopotamian Journal of Marine Sciences, 2019)
The present work presents key results for the effect of Karun River on the salinity status in the Shatt Al-Arab River, in which the Total Dissolved Solid could be described the salinity status. The salinization of water is a problem of many Rivers, especially, the Rivers of Iraq. The water of Shatt Al-Arab River in the south of Iraq is experiencing a salty problem due to the lack of freshwater discharges that started since the last decade of the last century due to anthropogenic and natural causes. The path of Karun River has been diverted temporary into the Iranian territory since 2009, which is the only stream into Shatt Al-Arab River at the southern part of its sharing course with Iran. However, there is a positive role of the temporary water releases from the Karun River in reducing the salinity of the water in some locations near the mouth and in the course of the Shatt Al-Arab River during Autumn and Winter and some months of the Spring. This has confirmed by the following-up of the behavior of salinity along the path of the River over the period 2008-2017.The present study showed that the monthly TDS rates at Shatt Al-Arab River stations (i.e. Basrah, Abu Al-Khaseb and Sehan) have affected by the Karun River releases. As there is a decrease in the values of TDS at Abu Al-Khaseb and Sehan stations during the high and low tide. However, the negative effect of Karun River occurred through increasing the TDS trends, and hence the salinity, during March and Summer.